THE PEDAGOGICAL VALUE OF PROVERBS AND SAYINGS IN ENGLISH LANGUAGE TEACHING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
Proverbs and sayings are essential elements of language that encapsulate cultural values, wisdom, and societal norms. In the context of English language teaching, incorporating proverbs and sayings can serve as a powerful tool for enhancing linguistic, cultural, and cognitive skills. This paper explores the pedagogical value of proverbs and sayings in English classes, focusing on their role in improving vocabulary, idiomatic understanding, cultural awareness, and critical thinking skills. Through an examination of teaching strategies and classroom activities, the study highlights best practices for integrating these linguistic elements into English language instruction. The findings suggest that proverbs and sayings not only facilitate language acquisition but also foster a deeper understanding of the cultural context in which the language is used, thereby enhancing overall communicative competence.